Geotecnologias na saúde: uma análise das doenças transmissíveis em Ituiutaba/MG, no período de 2009 a 2018. - Silva, Carlos Eduardo (2020)
With the instrumentalization of geography after the Second World War, it began to have a strong quantitative character. The use of software and hardware for space analysis created systems known as Geographic Information Systems (GIS). The general objective of the research was to analyze in the urban area of Ituiutaba / MG the occurrence of two conditions of compulsory notification, dengue and Accident with Venomous Animals (AAP), between the years 2009 and 2018, through geotechnologies. The first step in the research was to systematize the data on transile diseases that occurred in the city. These were made available by the Municipal Health Secretariat. After the identification of the main problems, the downtown district was chosen as the place of study since it had the highest rates. In addition, this area has historical and economic importance for the municipality, further justifying its study. The most evident result was the visualization of the distribution in almost the entire studied area of points considered important for the reduction of these diseases. The first relevant point raised was the wide distribution of vacant lots in the studied area. This makes the previously mentioned species circulate more easily, and consequently reproduce with greater speed.